Health communication strategies to address parental vaccine hesitancy regarding childhood vaccination in Nigeria: a systematic review - Tarela Juliet Ike; Dung Ezekiel Jidong; Callistar Kidochukwu Obi; Maureen Iru Ntaji; Mulugeta Tamire; Marekegn Habtamu; Mieyebi Lawrence Ike; Evangelyn Ebi Ayobi; Peremi Richmond Ike; Rukevwe Francis Doghor; Rakhshi Memon; Kelvin Odeyovwi Ayobi; et al. (Frontiers in Public Health, 2026)
Background Childhood vaccine hesitancy is a significant public health concern. In Nigeria, it remains a major barrier to achieving optimal immunization uptake, contributing to preventable morbidity and mortality. Yet there remains a significant research gap on the synthesis of health communication strategies to address parental hesitancy to childhood vaccination. The primary aim and original contribution of the present review is to synthesize health communication strategies to address parental hesitancy to childhood vaccination in Nigeria. Method The review strategy was underpinned by the Population, phenomenon of interest and context (PICo) model. Hence, the population (parents, carers, or primary caregivers of children between the ages of 0 and 3 years), the phenomenon of interest (health communication strategies to address parental hesitancy to childhood vaccination), and the context (vaccine hesitancy). For qualitative studies, the PICo strategy, which is a modified version of PICO, was used. Boolean operators (AND/OR/NOT) were used to ensure rigor in adopting informed search terms. Six databases were searched for published articles between 2017 and March 2026. N = 12 studies met the inclusion criteria, and the relevant data were synthesized and analyzed using a thematic synthesis approach. The review protocol was pre-registered on the PROSPERO Registry (no. CRD420261303323). Findings The synthesized studies and analyses yielded the following main findings: (i) Media campaign strategies, (ii) State-sponsored communication strategies, (iii) Community-centered strategies, and (iv) Phone-based strategies. Conclusion Childhood vaccine hesitancy remains a major challenge in Nigeria. The review recommends that vaccine communication be culturally attuned and multi-channeled (e.g., embedding community-centered mechanisms—particularly those involving trusted religious and traditional leaders, media platforms, and mobile phone text messaging). It also recommends that vaccine communication be responsive to both structural constraints and community information need to address parental hesitancy to childhood vaccine uptake.